Assessment for game-based learning - Ifenthaler, Dirk; Eseryel, D.; Ge, X. (2012)
Looking at the historical synopsis of games, an antagonism between games and work is noticeable. However, another important question is present: How can a game be beneficial for life? Games are classified as fully recreational games, serious games for informal context, serious games for formal context, and as assessment games. However, the implementation of assessment features into game-based learning environments is only in its early stages because it adds a very time-consuming step to the design process. Basically, assessment for game-based learning is distinguished between game scoring, external, and embedded assessment. Strength and weaknesses of assessment methodologies are discussed. The chapter concludes that intelligent assessment of game-based learning will be the challenges for the twenty-first century instructional designers and serious games developers.